Conocimientos y actitudes preventivas sobre el COVID19 en adolescentes de la jurisdicción de las IPRESS 6 de Octubre y Los Delfines, Iquitos 2023 - Garate Chavez, Roger Gabriel (2023)
Introduction: COVID 19 collapsed our health system, affecting the entire population, adolescents were a vulnerable group, not only at the socioeconomic and educational level, but also in their mental health, with low vaccination coverage. Objective: To determine the relationship between the level of knowledge and the preventive attitude about COVID19 in adolescents in the jurisdiction of the IPRESS 6 de Octubre and Los Delfines, in the city of Iquitos 2023. Methodology: Quantitative, descriptive, cross-sectional, prospective, correlational, interviewing 142 adolescents from the jurisdiction of the IPRESS 6 de Octubre and Los Delfines, applying a validated questionnaire to determine the level of knowledge and their preventive attitude about COVID19. Results: The level of knowledge of adolescents about COVID 19 was adequate in more than 50% and poor in 40%. Adolescents presented an adequate preventive attitude in more than 35% and inadequate in more than 60%. The good level of knowledge was significantly associated with the age of 16 to 19 years, with the female sex, a better educational level, having a family member with COVID 19 and having presented COVID 19. The adequate preventive attitude was significantly associated with age from 16 to 19 years old, with the female sex, a better educational level, having a family member with COVID 19 and having presented COVID 19. The level of knowledge is significantly related to the preventive attitude towards COVID 19. Conclusion: Adolescents present mostly an acceptable level of knowledge but an inadequate preventive attitude against COVID 19.